Imbalanced mobilities causing S-shaped IV curves in planar heterojunction organic solar cells - Tress, W; Petrich, A; Hummert, M; Hein, M; Leo, K; Riede, M (American Institute of Physics, 2011)
We show that S-kinks in the current voltage characteristics, which decrease the fill factor significantly, can be caused by a strong imbalance of charge carrier mobilities (hole mobility in donor and electron mobility in acceptor) in planar/flat heterojunction organic solar cells. Electrical simulations according to a drift-diffusion model predict the occurrence of an S-kink for a mobility mismatch factor larger than 100. By combining a low-mobility donor material, (1,2,3,4,9,10,11,12-octaphenyl-diindeno [1,2,3-cd: 1′,2′,3′-lm]perylene), with the acceptors C60 and N,N′-dimethylperylene-3,4:9,10-dicarboximide, which show different electron mobilities, we experimentally verify the predictions. Our results demonstrate that not only interface effects but also the photoactive material itself can cause S-kinks. © 2011 American Institute of Physics.